Low Energy Phosphorus Plasma Implantation for Isolation of MoS2 Devices. (3rd May 2017) - Haynes, Katherine; Murray, Ryan; Zhao, Xueying; Chiappe, Daniele; Sutar, Surajit; Radu, Iuliana; Hatem, Christopher; Perry, Scott; Jones, Kevin Scott
Abstract : Device isolation is a critical but overlooked challenge in the effort to assess MoS2 as a possible material for post-Si technology nodes. Although reactive ion etching or chemical etching can be used to create isolated channels in large-area films, these techniques are problematic due to the high density of dangling bonds that they create. In this study, radiation damage is presented as an alternative to physical isolation of MoS2 . Large-area ~4 layer MoS2 films were implanted by a low energy phosphine plasma at a bias of 200 V and a dose of 1 x 10 14 cm -2 . The results of this experiment indicate that there is greater than a 10 4 increase in sheet resistance of the MoS2 without measurable etching of the films. Annealing studies show that the resistance increase is stable up to at least 525°C, suggesting that radiation damage is an alternative to physical isolation for MoS2 devices.